De Novo Transcriptome Analysis of Durum Wheat Flag Leaves Provides New Insights Into the Regulatory Response to Elevated CO2 and High Temperature - Vicente, Rubén; Bolger, Anthony M.; Martínez-Carrasco, Rafael; Pérez, Pilar; Gutiérrez, Elena; Usadel, Björn; Morcuende, Rosa (Frontiers in Plant Science, 2019)
Global warming is becoming a significant problem for food security, particularly in the Mediterranean basin. The use of molecular techniques to study gene-level responses to environmental changes in non-model organisms is increasing and may help to improve the mechanistic understanding of durum wheat response to elevated CO2 and high temperature. With this purpose, we performed transcriptome RNA-seq analyses combined with physiological and biochemical studies in the flag leaf of plants grown in field chambers at ear emergence. Enhanced photosynthesis by elevated CO2 was accompained by an increase in biomass and starch and fructan content, and a decrease in N compounds, as chlorophyll, soluble proteins and Rubisco content, in association with a decline of nitrate reductase, initial and total Rubisco activities. Whilst high temperature led to a decline of chlorophyll, Rubisco activity and protein content, the glucose content increased and starch decreased. Furthermore, elevated CO2 induced several genes involved in mitochondrial electron transport, a few genes for photosynthesis and fructan synthesis, and most of the genes involved in secondary metabolism, gibberellin and jasmonate metabolism, whereas those related to light harvesting, nitrogen assimilation and other hormone pathways were repressed. High temperature repressed genes for carbon, energy, nitrogen, lipid, secondary and hormone metabolisms. Under the combined increases in atmospheric CO2 and temperature, the transcript profile resembled that previously reported for high temperature, although elevated CO2 partly alleviated the downregulation of primary and secondary metabolism genes. The results suggest that there was a reprogramming of primary and secondary metabolism under the future climatic scenario, leading to coordinated regulation of C-N metabolism towards carbon-rich metabolites at elevated CO2 and a shift away from carbon-rich secondary metabolites at high temperature. Several candidate genes differentially expressed were identified, including protein kinases, receptor kinases and transcription factors.